2009
DOI: 10.1164/rccm.200901-0118oc
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Receptor for Advanced Glycation End Products, Blood Transfusion, and Risk of Primary Graft Dysfunction

Abstract: Rationale:The receptor for advanced glycation end products (RAGE) is an important marker of lung epithelial injury and may be associated with impaired alveolar fluid clearance. We hypothesized that patients with primary graft dysfunction (PGD) after lung transplantation would have higher RAGE levels in plasma than patients without PGD. Objectives: To test the association of soluble RAGE (sRAGE) levels with PGD in a prospective, multicenter cohort study. Methods: We measured plasma levels of sRAGE at 6 and 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
107
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(121 citation statements)
references
References 42 publications
12
107
1
1
Order By: Relevance
“…The presence of autoimmunity immediately after lung transplantation in this group of patients is most likely representative of developing autoimmunity before lung transplantation, secondary to underlying lung disease. These observations are consistent with recent studies showing that interstitial lung diseases (among which idiopathic pulmonary fibrosis makes up the vast majority) pose a major risk factor for PGD (37). Reports from a number of investigators, including our group, have shown the presence of autoimmunity in the pathophysiology of idiopathic pulmonary fibrosis (38,39).…”
Section: Humoral Autoimmunity and Its Role In Obliterative Bronchiolitissupporting
confidence: 93%
“…The presence of autoimmunity immediately after lung transplantation in this group of patients is most likely representative of developing autoimmunity before lung transplantation, secondary to underlying lung disease. These observations are consistent with recent studies showing that interstitial lung diseases (among which idiopathic pulmonary fibrosis makes up the vast majority) pose a major risk factor for PGD (37). Reports from a number of investigators, including our group, have shown the presence of autoimmunity in the pathophysiology of idiopathic pulmonary fibrosis (38,39).…”
Section: Humoral Autoimmunity and Its Role In Obliterative Bronchiolitissupporting
confidence: 93%
“…A variety of clinical risk factors for PGD have been identified with contributions from the donor (3)(4)(5)(6)(7), the recipient (3)(4)(5)(7)(8)(9)(10), and operative variables (4,5,8,11). In addition, a number of biomarkers have been associated with increased risk of PGD, including markers of innate and adaptive immune activation, epithelial and endothelial injury, coagulation, vascular permeability, and lipid peroxidation (2,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Despite identification of these clinical and biomarker predictors of PGD, the mechanisms leading to PGD are not well understood, and there are no specific therapeutic interventions for PGD.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, recent reports suggest a predominant role of RAGE and its ligand HMGB1 in the initiation of lung IR injury (Sternberg, et al, 2008). In a multi-center study, Christie et al reported that an elevated plasma level of soluble RAGE (a truncated form of RAGE) was associated with primary graft dysfunction in patients undergoing lung transplantation (Christie, et al, 2009). An in depth characterization of the role of HMGB1, TLRs and RAGE remains to be elucidated in pulmonary injury after IR and transplantation.…”
Section: Receptor For Advanced Glycation End Products (Rage)mentioning
confidence: 96%